Impact of RhoA overexpression on clinical outcomes in cervical squamous cell carcinoma treated with concurrent chemoradiotherapy - Tanaka, Keiichi (J Radiat Res, 2020)
The Rho-associated coiled-coil-containing protein kinase (ROCK) pathway is known to influence metastasis in several cancers; however, the impact of the pathway on clinical outcomes in patients undergoing radiotherapy remains unknown. In the present study, the expression of RhoA, RhoC, ROCK-1, ROCK-2 and p53 was immunohistochemically evaluated using biopsy specimens obtained from 49 patients with stage II–III cervical squamous cell carcinoma treated with concurrent chemoradiotherapy (CCRT). The relationship between the expression of these proteins and patient outcomes was investigated. RhoA overexpression was associated with significantly impaired disease-free survival and distant metastasis-free survival (P = 0.045 and P = 0.041, respectively) in stage III cancer patients. No differences in survival were observed based on the expression of the other proteins among stage III cancer patients. In stage II cancer patients, no differences in survival were noted based on the expression of any of the proteins. The expression of RhoA was able to successfully differentiate cervical cancer patients with distant metastasis after CCRT. This information may help stratify patients according to the risk of metastasis, thereby leading to the potential to provide individualized treatment.